PENGARUH CARA DISTRIBUSI PENCAHAYAAN BUATAN PADA KENYAMANAN BERCENGKERAMA PENGUNJUNG KAFE - MARTIN SENA KRISTIAN; LEONARDO .; ERWIN ARDIANTO HALIM (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2018)
Nowadays, young people like Cafe more as a place for socializing than merely for eating. Its environment is made to comfort them through lighting design. This research aims to describe lighting distribution type from users choice of comfort while socializing in a cafÃ©. The method is to ask 60 persons to choose the most comfortable lighting environment from five given illustrations based on a theory by ILO (1998) and Grondzik and Kwok (2010) theory. The result shows indirect lighting from wall and ceiling as the most preferred lighting distribution to support comfort while socializing.